Dedicated protection of multicast sessions in mixed-graph sparse-splitting optical networks - Gomes, Teresa (2017)
This work addresses the problem of dedicated protection of multicast sessions in mixed-graph optical networks, where only a fraction of the nodes have optical splitting capabilities. A novel multicast routing algorithm for sparse splitting optical networks (the Modified Steiner Tree Heuristic (MSTH)) is initially presented and is subsequently utilized (together with two existing heuristics (MUS and MSH)) by an effective scheme for the calculation of a pair of disjoint trees. The key idea of this New Arc-Disjoint Trees (NADT) protection technique is to gradually construct the primary tree, verifying that after the addition of each one of the destinations of the multicast session, a secondary (arc-disjoint) tree can still be obtained. Performance results demonstrate that the proposed NADT protection technique clearly outperforms the conventional Arc-Disjoint Trees (ADT) approach in terms of blocking ratio, while incurring only a negligible increase of the average cost of the derived pair of arc-disjoint trees. Furthermore, it is shown that the newly proposed algorithm, MSTH-NADT, is the one having the best performance in terms of cost and blocking, with MSH-NADT having similar, albeit slightly worse, performance. However, as MSH-NADT requires much less CPU time compared to MSTH-NADT, MSH-NADT can be considered the best compromise technique.